Tools for High Performance Computing Proceedings of the 2nd International Workshop on Parallel Tools for High Performance Computing, July 2008, HLRS, Stuttgart - Resch, Michael; Keller, Rainer; Himmler, Valentin; Krammer, Bettina; Schulz, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
With the advent of multi-core processors, implementing parallel programming methods in application development is absolutely necessary in order to achieve good performance. Soon, 8-core and possibly 16-core processors will be available, even for desktop machines. To support application developers in the various tasks involved in this process, several different tools need to be at his or her disposal. This workshop will give the users an overview of the existing tools in the area of integrated development environments for clusters, various parallel debuggers, and new-style performance analysis tools, as well as an update on the state of the art of long-term research tools, which have advanced to an industrial level. The proceedings of the 2nd Parallel Tools Workshop guide participants by providing a technical overview to help them decide upon which tool suits the requirements for the development task at hand. Additionally, through the hands-on sessions, the workshop will enable the user to immediately deploy the tools.
Integrated Development Environments -- Sun HPC ClusterTools$1!" (B7+: A Binary Distribution of Open MPI -- An Integrated Environment For the Development of Parallel Applications -- Debugging MPI Programs on the Grid using g-Eclipse -- Parallel Communication and Debugging -- Enhanced Memory debugging of MPI-parallel Applications in Open MPI -- MPI Correctness Checking with Marmot -- Memory Debugging in Parallel and Distributed Applications -- Performance Analysis Tools -- Sequential Performance Analysis with Callgrind and KCachegrind -- Improving Cache Utilization Using Acumem VPE -- Parallel Performance Analysis Tools -- The Vampir Performance Analysis Tool-Set -- Usage of the SCALASCA toolset for scalable performance analysis of large-scale parallel applications -- Evolution of a Parallel Performance System -- Cray Performance Analysis Tools.s
Keywords: Computer science; Architecture, Computer; Software engineering; Computers; Complexity, Computational; Computer Science; Theory of Computation; Software Engineering/Programming and Operating Systems; Computer System Implementation; Complexity; Electronic books